How soil carbon accounting can improve to support investment- oriented actions promoting soil carbon storage - Costa, Ciniro; Dittmer, Kyle M.; Shelton, Sadie W.; Bossio, Deborah A.; Zinyengere, Nkulumo; Luu, Paul; Heinz, Sebastian; Egenolf, Konrad; Rowland, Bailey; Zuluaga, Andrés; Klemme, Julia; Mealey, Tim; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Key messages ◼ The financial community needs a standardized, low-cost, fit-for-purpose approach to soil organic carbon (SOC) accounting that encourages investment and adapts to the climate market. ◼ To encourage investments, an accounting system should provide “value for money,” align with global goals and support co-benefits, while safeguarding reputational risks. ◼ Building a sequenced approach to improve accounting accuracy requires planning to reduce uncertainties of the accounting systems overtime. ◼ Developing low-cost SOC accounting requires i) focusing on a few high-quality direct measurements (opposed to multiple low-quality measurements), ii) reducing the uncertainty of models, and iii) enhancing capability to easily incorporate farm-level activity data. ◼ Moving to hybrid measurement approaches (a mix of direct measurements with modeling and remote sensing) seems to be the most cost-effective pathway to achieve low-cost SOC accounting systems.